Offering the “Sociological Eye” to Examine Ethical Egoism at an Illustrative Homeless Shelter for Men: A Pedagogical Exercise - Farmer, J. Forbes (Advances in Social Sciences Research Journal, 2019)
This is an exploration into the philosophical realm of misplaced ethics at an illustrative homeless shelter where human service practitioners should be keeping better focus on delivering services to destitute men in a large industrial city. The question raised is whether or not the cause of the ethical egoism seen there, that results in problems typical of homeless shelters around the world, is structurally based. The problems result in mistrust of the shelter and a diminishment of services to a vulnerable population. Sociologically framed questions serve as a tool for the use of the case method of teaching.